Design, synthesis and biological evaluation of pyrazolo[3,4-d]pyridazinone derivatives as covalent FGFR inhibitors - Xiaowei Wu; Mengdi Dai; Rongrong Cui; Yulan Wang; Chunpu Li; Xia Peng; Jihui Zhao; Bao Wang; Yang Dai; Dan Feng; Tianbiao Yang; Hualiang Jiang; et al. (Elsevier, 2021)
Fibroblast growth factor receptors (FGFRs) have emerged as promising targets for anticancer therapy. In this study, we synthesized and evaluated the biological activity of 66 pyrazolo[3,4-d]pyridazinone derivatives. Kinase inhibition, cell proliferation, and whole blood stability assays were used to evaluate their activity on FGFR, allowing us to explore structure−activity relationships and thus to gain understanding of the structural requirements to modulate covalent inhibitors' selectivity and reactivity. Among them, compound 10h exhibited potent enzymatic activity against FGFR and remarkably inhibited proliferation of various cancer cells associated with FGFR dysregulation, and suppressed FGFR signaling pathway in cancer cells by the immunoblot analysis. Moreover, 10h displayed highly potent antitumor efficacy (TGI = 91.6%, at a dose of 50 mg/kg) in the FGFR1-amplified NCI-H1581 xenograft model.